Environment-friendly anti-radiation coating for building and preparation method thereof
By mixing epoxy resin, vegetable oil and tetrabutyl ammonium bromide under nitrogen protection, and adding activated titanium dioxide and graphene oxide to form an efficient and environmentally friendly radiation-proof coating, the existing coatings have solved the problems of weak radiation resistance, poor environmental protection and poor stability, and achieved a significant improvement in radiation-proof performance and stability.
Patent Information
- Application Number
- CN202411886648.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing radiation-proof coatings for construction have weak radiation resistance, their components are not environmentally friendly and their stability is poor.
The mixture of epoxy resin, vegetable oil and tetrabutyl ammonium bromide under nitrogen protection, para-hydroxyanisole and acrylic acid were added, and activated titanium dioxide and graphene oxide were added. After decompression distillation and wet ball milling, an efficient environmentally friendly radiation-proof coating was formed.
It significantly improves the radiation resistance and stability of the paint, enhances the crack resistance and heat resistance of the paint, and is environmentally friendly in materials, suitable for large-scale promotion.
Smart Images

Figure CN119592177A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an environmentally friendly radiation-proof coating for buildings and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology, electromagnetic pollution has been recognized as the fourth largest public hazard after air pollution, water pollution and noise pollution. The United Nations Conference on the Human Environment has listed electromagnetic radiation as one of the main pollutants that must be controlled.
[0003] Electromagnetic waves are colorless, odorless, and invisible. They can penetrate a variety of substances, including the human body. If the human body is exposed to radiation doses exceeding the safe level for a long time, cells will be injured or killed on a large scale. As buildings are the main places for human work and life, the use of radiation-proof electromagnetic shielding materials on building envelopes can not only prevent internal electromagnetic sources from propagating outward, but also prevent external electromagnetic waves from entering the building. It is an effective way to suppress electromagnetic leakage and interference and reduce radiation hazards. Therefore, the demand for radiation-proof coatings is also increasing.
[0004] Anti-radiation coatings were first used in the military field, and later in civilian use to protect the human body and electronic equipment from harm and interference from electromagnetic waves. Applying anti-radiation coatings on the surface of buildings can block and reduce electromagnetic radiation. The main disadvantages of the anti-radiation coatings currently used on building surfaces are weak radiation protection, unenvironmentally friendly ingredients, and poor stability. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an environmentally friendly radiation-proof coating for construction and a preparation method thereof.
[0006] A method for preparing an environmentally friendly radiation-proof coating for construction comprises the following steps:
[0007] S1. Under nitrogen protection, 50-100 parts of epoxy resin, 30-50 parts of vegetable oil, and 3-5 parts of tetrabutylammonium bromide are mixed uniformly by weight, the temperature is raised to 105-115° C., 1-2 parts of p-hydroxyanisole are added and stirred for 5-10 hours, the temperature is lowered to 85-95° C., 10-20 parts of acrylic acid are added dropwise for 0.5-1 hour, and the reaction is continued for 7-8 hours after the addition is complete, the temperature is lowered to room temperature, 5-10 parts of barium sulfate powder are added, and the mixture is stirred for 10-12 hours to obtain preform A;
[0008] S2, adding 5-10 parts of nano carbon sphere template to 50-80 parts of 40-60% ethanol aqueous solution, stirring at a speed of 100-500r / min for 10-20min, adjusting the system temperature to 50-60°C, adding 5-15 parts of tetrabutyl titanate thereto under stirring, continuing stirring for 2-6h, centrifuging, calcining at a temperature of 400-500°C in an air atmosphere for 1-2h, adding 0.1-0.5 parts of titanate coupling agent to 20-40 parts of 40-60% ethanol aqueous solution, stirring at a temperature of 40-60°C for 4-7h, centrifuging, washing, adding to N,N-dimethylformamide, adding 1-2 parts of succinic anhydride, stirring at a temperature of 40-50°C for 1-2h, adding 1-3 parts of graphene oxide, stirring for 2-10h, centrifuging, washing, and vacuum drying to obtain activated titanium dioxide;
[0009] S3, 5-10 parts of silicone resin, 5-10 parts of methyltriethoxysilane, 5-10 parts of 3-aminopropyltriethoxysilane, and activated titanium dioxide are distilled under reduced pressure for 1-2 hours, added to preform A and stirred at a stirring speed of 200-400 r / min for 1-2 hours, and distilled under reduced pressure for 1-2 hours to obtain preform B;
[0010] S4. Add 1-3 parts of ultrafine bismuth oxide, 1-3 parts of surfactant, 1-3 parts of cobalt cyclohexaneate, 1-3 parts of melamine pyrophosphate, 10-15 parts of propylene glycol, and 1-3 parts of perlite to prefabricated material B, stir evenly, and wet-ball-mill to obtain an environmentally friendly radiation-proof coating for construction.
[0011] Preferably, in S1, the vegetable oil is linseed oil or castor oil.
[0012] Preferably, in S1, the particle size of the barium sulfate powder is 0.1-0.2 μm.
[0013] Preferably, in S2, the particle size of the nano carbon sphere template is 100-200 nm.
[0014] Preferably, in S2, the titanate coupling agent is dioctyl pyrophosphoryl titanate.
[0015] Preferably, in S2, the particle size of graphene oxide is 10-20 μm.
[0016] Preferably, in S3, the silicone resin is an environmentally friendly phenyl silicone resin.
[0017] Preferably, in S4, the particle size of the ultrafine bismuth oxide is 0.1-0.2 μm.
[0018] Preferably, in S4, the surfactant is fatty acyl diethanolamine.
[0019] Preferably, an environmentally friendly radiation-proof coating for construction is prepared by the method for preparing the environmentally friendly radiation-proof coating for construction.
[0020] Beneficial effects:
[0021] The present invention uses renewable plant oil as epoxy resin modifier, compounded with acrylic acid, and mixed and modified each other, which not only has a high cross-linking density and effectively improves the heat resistance of the system, but also ensures the adhesion strength of the coating.
[0022] If graphene oxide and nano-titanium dioxide are simply compounded, it can be beneficial to improve multiple reflection loss, but its filling amount is difficult to achieve a large amount. The present invention uses a nano-carbon ball template as a template, and the obtained spherical hollow nano-titanium dioxide not only has a complete sphere, but also has good monodispersity. After its surface is carboxylated and modified, it has a high bonding strength with graphene oxide. The graphene oxide structure with a one-dimensional sheet structure and the spherical hollow nano-titanium dioxide produce a synergistic effect, which can effectively improve the dispersion uniformity, and then mixed and modified with an organic silicon polymer to increase its filling amount in the system, and can effectively improve the heat resistance of the system, and its special structure is conducive to further improving multiple reflection loss.
[0023] This application combines graphene oxide with spherical hollow nano-titanium dioxide structures, which can achieve more uniform connection between graphene oxides in the system, effectively form conductive paths, multiple reflection losses, and make it difficult for electromagnetic radiation to quickly penetrate after entering, significantly improving the radiation protection performance of the coating. Through experiments, it was found that the present invention can effectively improve the radiation protection of the system, with excellent radiation protection stability, and at the same time improve the crack resistance of the coating after it is applied to the surface of the building, and it is not easy to crack and fall off.
[0024] The present invention effectively overcomes the shortcomings of radiation protection materials such as easy decomposition, easy migration and uneven dispersion, can significantly improve the radiation resistance of the coating itself, and at the same time has excellent heat resistance and strength. Even if exposed to the natural environment, the service life is not easily shortened. The preparation method is simple and suitable for large-scale promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a comparison chart of the shielding rates of the environmentally friendly radiation-proof coatings obtained using Example 5 and Comparative Examples 1-2.
[0026] Figure 2 This is a comparison chart of the impact strength of the environmentally friendly radiation-proof coatings obtained using Example 5 and Comparative Examples 1-2.
[0027] Figure 3 This is a comparison chart of the bonding strength of the environmentally friendly radiation-proof coatings obtained using Example 5 and Comparative Examples 1-2.
[0028] Figure 4This is a comparison chart of the heat loss rates of the environmentally friendly radiation-proof coatings obtained using Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0029] The present invention will be further explained below in conjunction with specific embodiments.
[0030] The nano carbon sphere template used below was purchased from Qinghe Chaotai Metal Materials Co., Ltd.; the graphene oxide used below was purchased from Jiangsu Xianfeng Nanotechnology Co., Ltd.; the environmentally friendly phenyl silicone resin used below was purchased from Shandong Dayi Chemical Co., Ltd.; the epoxy resin model used below was E51, purchased from Shandong Dayi Chemical Co., Ltd. The titanate coupling agent used below was purchased from Wuhan Kanos Technology Co., Ltd.
[0031] Example 1
[0032] A method for preparing an environmentally friendly radiation-proof coating for construction comprises the following steps:
[0033] S1. Under nitrogen protection, 50g epoxy resin, 30g linseed oil and 3g tetrabutylammonium bromide were mixed evenly, the temperature was raised to 115°C, 1g p-hydroxyanisole was added and stirred for 5h, the temperature was lowered to 85°C, 10g acrylic acid was added dropwise for 1h, and the reaction was continued for 8h after the addition was complete, the temperature was lowered to room temperature, 5g barium sulfate powder with a particle size of 0.2μm was added, and stirred for 10h to obtain preform A;
[0034] S2, add 5g of nano carbon sphere template with a particle size of 100nm to 50g of 60% ethanol aqueous solution, stir at a speed of 500r / min for 20min, adjust the system temperature to 60℃, add 5g of tetrabutyl titanate thereto under stirring, continue stirring for 2h, centrifuge, calcine at 500℃ in air atmosphere for 2h, add 0.1g of dioctyl pyrophosphoryl titanate to 20g of 60% ethanol aqueous solution, stir at 60℃ for 4h, centrifuge, wash, add to 20g of N,N-dimethylformamide, add 1g of succinic anhydride, stir at 50℃ for 1h, add 1g of graphene oxide with a particle size of 10μm, stir for 2h, centrifuge, wash, and vacuum dry to obtain activated titanium dioxide;
[0035] S3, 5g of environmentally friendly phenyl silicone resin, 5g of methyltriethoxysilane, 5g of 3-aminopropyltriethoxysilane, and activated titanium dioxide were distilled under reduced pressure for 1-2h, added to preform A and stirred at a stirring speed of 400r / min for 2h, and distilled under reduced pressure for 2h to obtain preform B;
[0036] S4. Add 1g of ultrafine bismuth oxide with a particle size of 0.1μm, 1g of fatty acyl diethanolamine, 1g of cobalt cyclopentaneate, 1g of melamine pyrophosphate, 10g of propylene glycol, and 1g of perlite with a particle size of 10μm to prefabricated material B and stir evenly. Add the prefabricated material to a planetary wet ball mill for wet grinding at a wet grinding stirring speed of 600r / min and a stirring time of 1h to obtain an environmentally friendly radiation-proof coating for construction.
[0037] Example 2
[0038] A method for preparing an environmentally friendly radiation-proof coating for construction comprises the following steps:
[0039] S1. Under nitrogen protection, 100 g of epoxy resin, 50 g of castor oil and 5 g of tetrabutylammonium bromide were mixed evenly, the temperature was raised to 115 ° C, 2 g of p-hydroxyanisole was added and stirred for 5 h, the temperature was lowered to 85 ° C, 20 g of acrylic acid was added dropwise for 1 h, and the reaction was continued for 8 h after the addition was complete, the temperature was lowered to room temperature, 10 g of barium sulfate powder with a particle size of 0.2 μm was added, and the mixture was stirred for 10 h to obtain preform A;
[0040] S2, add 10g of nano carbon sphere template with a particle size of 100nm to 80g of 60% ethanol aqueous solution, stir at a speed of 500r / min for 20min, adjust the system temperature to 60℃, add 15g of tetrabutyl titanate thereto under stirring, continue stirring for 2h, centrifuge, calcine at 500℃ in air atmosphere for 2h, add 0.5g of dioctyl pyrophosphoryl titanate to 40g of 60% ethanol aqueous solution, stir at 60℃ for 4h, centrifuge, wash, add to 40g of N,N-dimethylformamide, add 2g of succinic anhydride, stir at 50℃ for 1h, add 3g of graphene oxide with a particle size of 10μm, stir for 2h, centrifuge, wash, and vacuum dry to obtain activated titanium dioxide;
[0041] S3, 10g of environmentally friendly phenyl silicone resin, 10g of methyltriethoxysilane, 10g of 3-aminopropyltriethoxysilane, and activated titanium dioxide were distilled under reduced pressure for 1-2h, added to preform A and stirred at a stirring speed of 400r / min for 2h, and distilled under reduced pressure for 2h to obtain preform B;
[0042] S4. Add 3g of ultrafine bismuth oxide with a particle size of 0.1μm, 3g of fatty acyl diethanolamine, 3g of cobalt cyclopentaneate, 3g of melamine pyrophosphate, 15g of propylene glycol, and 3g of perlite with a particle size of 10μm to prefabricated material B and stir evenly. Add the prefabricated material to a planetary wet ball mill for wet grinding at a wet grinding stirring speed of 600r / min and a stirring time of 1h to obtain an environmentally friendly radiation-proof coating for construction.
[0043] Example 3
[0044] A method for preparing an environmentally friendly radiation-proof coating for construction comprises the following steps:
[0045] S1. Under nitrogen protection, 51g epoxy resin, 31g linseed oil and 3.1g tetrabutylammonium bromide were mixed evenly, the temperature was raised to 115°C, 1.1g p-hydroxyanisole was added and stirred for 5h, the temperature was lowered to 85°C, 11g acrylic acid was added dropwise for 1h, and the reaction was continued for 8h after the addition was complete, the temperature was lowered to room temperature, 5.1g barium sulfate powder with a particle size of 0.2μm was added, and stirred for 10h to obtain preform A;
[0046] S2, add 5.1g of nano carbon sphere template with a particle size of 100nm to 51g of 60% ethanol aqueous solution, stir at a speed of 500r / min for 20min, adjust the system temperature to 60℃, add 5.1g of tetrabutyl titanate thereto under stirring, continue stirring for 2h, centrifuge, calcine at 500℃ in air atmosphere for 2h, add 0.11g of dioctyl pyrophosphoryl titanate to 21g of 60% ethanol aqueous solution, stir at 60℃ for 4h, centrifuge, wash, add to 21g of N,N-dimethylformamide, add 1.1g of succinic anhydride, stir at 50℃ for 1h, add 1.1g of graphene oxide with a particle size of 10μm, stir for 2h, centrifuge, wash, and vacuum dry to obtain activated titanium dioxide;
[0047] S3, 5.1g of environmentally friendly phenyl silicone resin, 5.1g of methyltriethoxysilane, 5.1g of 3-aminopropyltriethoxysilane, and activated titanium dioxide were distilled under reduced pressure for 1-2h, added to preform A and stirred at a stirring speed of 400r / min for 2h, and distilled under reduced pressure for 2h to obtain preform B;
[0048] S4. Add 1.1 g of ultrafine bismuth oxide with a particle size of 0.1 μm, 1.1 g of fatty acyl diethanolamine, 1.1 g of cobalt cyclopentaneate, 1.1 g of melamine pyrophosphate, 11 g of propylene glycol, and 1.1 g of perlite with a particle size of 10 μm to prefabricated material B and stir evenly. Add the prefabricated material to a planetary wet ball mill and grind it in a wet grinding process at a stirring speed of 600 r / min for 1 h to obtain an environmentally friendly radiation-proof coating for construction.
[0049] Example 4
[0050] A method for preparing an environmentally friendly radiation-proof coating for construction comprises the following steps:
[0051] S1. Under nitrogen protection, 99g of epoxy resin, 49g of linseed oil and 4.9g of tetrabutylammonium bromide were mixed evenly, the temperature was raised to 115°C, 2.9g of p-hydroxyanisole was added and stirred for 5h, the temperature was lowered to 85°C, 19g of acrylic acid was added dropwise for 1h, and the reaction was continued for 8h after the addition was complete, the temperature was lowered to room temperature, 9g of barium sulfate powder with a particle size of 0.2μm was added, and the mixture was stirred for 10h to obtain preform A;
[0052] S2, adding 9g of nano carbon sphere template with a particle size of 100nm to 79g of 60% ethanol aqueous solution, stirring at a speed of 500r / min for 20min, adjusting the system temperature to 60°C, adding 14g of tetrabutyl titanate thereto under stirring, continuing stirring for 2h, centrifuging, calcining at a temperature of 500°C in an air atmosphere for 2h, adding 0.49g of dioctyl pyrophosphoryl titanate to 39g of 60% ethanol aqueous solution, stirring at a temperature of 60°C for 4h, centrifuging, washing, adding to 19g of N,N-dimethylformamide, adding 1.9g of succinic anhydride, stirring at a temperature of 50°C for 1h, adding 2.9g of graphene oxide with a particle size of 10μm, stirring for 2h, centrifuging, washing, and vacuum drying to obtain activated titanium dioxide;
[0053] S3, 9.9g of environmentally friendly phenyl silicone resin, 9.9g of methyltriethoxysilane, 9.9g of 3-aminopropyltriethoxysilane, and activated titanium dioxide were distilled under reduced pressure for 1-2h, added to preform A and stirred at a stirring speed of 400r / min for 2h, and distilled under reduced pressure for 2h to obtain preform B;
[0054] S4. Add 2.9 g of ultrafine bismuth oxide with a particle size of 0.1 μm, 2.9 g of fatty acyl diethanolamine, 2.9 g of cobalt cyclopentaneate, 2.9 g of melamine pyrophosphate, 14 g of propylene glycol, and 2.9 g of perlite with a particle size of 10 μm to prefabricated material B and stir evenly. Add the prefabricated material to a planetary wet ball mill and grind it wet at a speed of 600 r / min for 1 h to obtain an environmentally friendly radiation-proof coating for construction.
[0055] Example 5
[0056] A method for preparing an environmentally friendly radiation-proof coating for construction comprises the following steps:
[0057] S1. Under nitrogen protection, 75g of epoxy resin, 40g of linseed oil and 4g of tetrabutylammonium bromide were mixed evenly, the temperature was raised to 115°C, 1.5g of p-hydroxyanisole was added and stirred for 5h, the temperature was lowered to 85°C, 15g of acrylic acid was added dropwise for 1h, and the reaction was continued for 8h after the addition was complete, the temperature was lowered to room temperature, 8g of barium sulfate powder with a particle size of 0.2μm was added, and the mixture was stirred for 10h to obtain preform A;
[0058] S2, add 8g of nano carbon sphere template with a particle size of 100nm to 65g of 60% ethanol aqueous solution, stir at a speed of 500r / min for 20min, adjust the system temperature to 60℃, add 10g of tetrabutyl titanate thereto under stirring, continue stirring for 2h, centrifuge, calcine at 500℃ in air atmosphere for 2h, add 0.3g of dioctyl pyrophosphoryl titanate to 30g of 60% ethanol aqueous solution, stir at 60℃ for 4h, centrifuge, wash, add to 30g N,N-dimethylformamide, add 1.5g of succinic anhydride, stir at 50℃ for 1h, add 3g of graphene oxide with a particle size of 10μm, stir for 2h, centrifuge, wash, and vacuum dry to obtain activated titanium dioxide;
[0059] S3, 8g of environmentally friendly phenyl silicone resin, 8g of methyltriethoxysilane, 8g of 3-aminopropyltriethoxysilane, and activated titanium dioxide were distilled under reduced pressure for 1-2h, added to preform A and stirred at a stirring speed of 400r / min for 2h, and distilled under reduced pressure for 2h to obtain preform B;
[0060] S4. Add 2 g of ultrafine bismuth oxide with a particle size of 0.1 μm, 2 g of fatty acyl diethanolamine, 2 g of cobalt cyclopentaneate, 2 g of melamine pyrophosphate, 10 g of propylene glycol, and 2 g of perlite with a particle size of 10 μm to prefabricated material B and stir evenly. Add the prefabricated material to a planetary wet ball mill for wet grinding at a wet grinding stirring speed of 600 r / min and a stirring time of 1 h to obtain an environmentally friendly radiation-proof coating for construction.
[0061] Comparative Example 1
[0062] A method for preparing an environmentally friendly radiation-proof coating for construction comprises the following steps:
[0063] S1. Under nitrogen protection, 75g of epoxy resin, 40g of linseed oil and 4g of tetrabutylammonium bromide were mixed evenly, the temperature was raised to 115°C, 1.5g of p-hydroxyanisole was added and stirred for 5h, the temperature was lowered to 85°C, 15g of acrylic acid was added dropwise for 1h, and the reaction was continued for 8h after the addition was complete, the temperature was lowered to room temperature, 8g of barium sulfate powder with a particle size of 0.2μm was added, and the mixture was stirred for 10h to obtain preform A;
[0064] S2, add 8g of nano carbon sphere template with a particle size of 100nm to 65g of 60% ethanol aqueous solution, stir at a speed of 500r / min for 20min, adjust the system temperature to 60℃, add 10g of tetrabutyl titanate thereto under stirring, continue stirring for 2h, centrifuge, calcine at 500℃ in air atmosphere for 2h, add 0.3g of dioctyl pyrophosphoryl titanate to 30g of 60% ethanol aqueous solution, stir at 60℃ for 4h, centrifuge, wash, add to 30g N,N-dimethylformamide, add 1.5g of succinic anhydride, stir at 50℃ for 1h, stir for 2h, centrifuge, wash, and vacuum dry to obtain activated titanium dioxide;
[0065] S3, 8g of environmentally friendly phenyl silicone resin, 8g of methyltriethoxysilane, 8g of 3-aminopropyltriethoxysilane, and activated titanium dioxide were distilled under reduced pressure for 1-2h, added to preform A and stirred at a stirring speed of 400r / min for 2h, and distilled under reduced pressure for 2h to obtain preform B;
[0066] S4. Add 2 g of ultrafine bismuth oxide with a particle size of 0.1 μm, 3 g of graphene oxide with a particle size of 10 μm, 2 g of fatty acyl diethanolamine, 2 g of cobalt cyclopentaneate, 2 g of melamine pyrophosphate, 10 g of propylene glycol, and 2 g of perlite with a particle size of 10 μm to prefabricated material B and stir evenly. Add the prefabricated material to a planetary wet ball mill for wet grinding at a wet grinding stirring speed of 600 r / min and a stirring time of 1 h to obtain an environmentally friendly radiation-proof coating for construction.
[0067] Comparative Example 2
[0068] A method for preparing an environmentally friendly radiation-proof coating for construction comprises the following steps:
[0069] S1. Under nitrogen protection, 75g of epoxy resin, 40g of linseed oil and 4g of tetrabutylammonium bromide were mixed evenly, the temperature was raised to 115°C, 1.5g of p-hydroxyanisole was added and stirred for 5h, the temperature was lowered to 85°C, 15g of acrylic acid was added dropwise for 1h, and the reaction was continued for 8h after the addition was complete, the temperature was lowered to room temperature, 8g of barium sulfate powder with a particle size of 0.2μm was added, and the mixture was stirred for 10h to obtain preform A;
[0070] S2, add 10g of tetrabutyl titanate to 65g of 60% ethanol aqueous solution, stir at a speed of 500r / min, adjust the system temperature to 60°C, stir for 2h, add 0.3g of dioctyl pyrophosphoryl titanate to 30g of 60% ethanol aqueous solution, stir at 60°C for 4h, centrifuge, wash, add to 30g of N,N-dimethylformamide, add 1.5g of succinic anhydride, stir at 50°C for 1h, add 3g of graphene oxide with a particle size of 10μm, stir for 2h, centrifuge, wash, and vacuum dry to obtain activated titanium dioxide;
[0071] S3, 8g of environmentally friendly phenyl silicone resin, 8g of methyltriethoxysilane, 8g of 3-aminopropyltriethoxysilane, and activated titanium dioxide were distilled under reduced pressure for 1-2h, added to preform A and stirred at a stirring speed of 400r / min for 2h, and distilled under reduced pressure for 2h to obtain preform B;
[0072] S4. Add 2 g of ultrafine bismuth oxide with a particle size of 0.1 μm, 2 g of fatty acyl diethanolamine, 2 g of cobalt cyclopentaneate, 2 g of melamine pyrophosphate, 10 g of propylene glycol, and 2 g of perlite with a particle size of 10 μm to prefabricated material B and stir evenly. Add the prefabricated material to a planetary wet ball mill for wet grinding at a wet grinding stirring speed of 600 r / min and a stirring time of 1 h to obtain an environmentally friendly radiation-proof coating for construction.
[0073] test
[0074] The environmentally friendly radiation-proof coatings prepared in Example 5 and Comparative Examples 1-2 were divided into Example 5 group and Comparative Examples 1-2 group, and the following tests were performed respectively.
[0075] Radiation protection performance test
[0076] The environmentally friendly radiation-proof coatings of Example 1-5 and Comparative Example 1-2 were coated on clean and dry thin steel plates, and then placed at room temperature for 24 hours for curing before testing the relevant performance. The thin steel plates used in the test were flat, free of mechanical defects such as indentations and pits, and were degreased and rust-removed to ensure that the surface of the thin steel plates was clean and dry. The samples coated with each group of coatings (coating thickness of 50±1μm) were tested for 241Am (241Am59.5kev energy peak) using a portable low-background gamma spectrometer to measure their shielding rate.
[0077] In order to reduce background interference, blank samples should be tested first as blank groups.
[0078] The shielding rates were tested 1-3 months after the samples were placed.
[0079] The test results are as follows Figure 1As shown, the shielding rate of Example 5 is the largest, which is better than that of Comparative Examples 1-2 and the blank group.
[0080] Impact strength test
[0081] According to GB / T1732-2020 standard, the environmentally friendly radiation protection coatings of Example 1-5 and Comparative Example 1-2 were respectively applied to 150×70×0.28mm tinplate test plates with a thickness of 1mm and cured for 7 days. The test plate was placed flat on the base using a positive impact tester, and the hammer controller was adjusted at different heights to make the hammer head fall freely. The test plate was taken out to observe whether the coating had cracks, wrinkles and peeling, and the height of the cracks in the coating was recorded.
[0082] The test results are as follows Figure 2 As shown, Example 5 has the largest crack height and the greatest impact strength, both of which are better than Comparative Examples 1-2.
[0083] Bond strength test
[0084] According to HG / T4567-2013 standard, fill the mortar block (70×70×20mm) with a mold frame (internal dimensions 40×40×2mm), use a scraper to make the surface flat, remove the mold frame, and cure for 14 days at room temperature. During the 10th day, apply adhesive evenly on the surface of the coating and place a steel fixture, remove excess adhesive around, and after curing for the specified time, use a tensile testing machine at a tensile speed of 5mm / min to test the maximum tensile load.
[0085] The test results are as follows Figure 3 As shown, the bonding strength of Example 5 is the largest, which is better than that of Comparative Examples 1-2.
[0086] Thermal stability test
[0087] The thermal stability of the coating was tested using a TGA / DSC1 thermogravimetric analyzer from Mettler, Switzerland, with a temperature range of 25-625°C, a heating rate of 10°C / min, and the mass was recorded every 200°C to obtain the heat loss rate. Before the test, the samples were dried at room temperature for 12 hours.
[0088] The test results are as follows Figure 4 As shown, the heat loss rate of Example 5 is the smallest at different temperatures, which is better than that of Comparative Examples 1-2.
[0089] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an environmentally friendly radiation-proof coating for construction, characterized in that: The following steps are involved: S1. Under nitrogen protection, 50-100 parts of epoxy resin, 30-50 parts of vegetable oil, and 3-5 parts of tetrabutylammonium bromide are mixed uniformly by weight, the temperature is raised to 105-115° C., 1-2 parts of p-hydroxyanisole are added and stirred for 5-10 hours, the temperature is lowered to 85-95° C., 10-20 parts of acrylic acid are added dropwise for 0.5-1 hour, and the reaction is continued for 7-8 hours after the addition is complete, the temperature is lowered to room temperature, 5-10 parts of barium sulfate powder are added and stirred for 10-12 hours to obtain preform A; S2, adding 5-10 parts of nano carbon sphere template to 50-80 parts of 40-60% ethanol aqueous solution, stirring at a speed of 100-500r / min for 10-20min, adjusting the system temperature to 50-60°C, adding 5-15 parts of tetrabutyl titanate thereto under stirring, continuing stirring for 2-6h, centrifuging, calcining at a temperature of 400-500°C in an air atmosphere for 1-2h, adding 0.1-0.5 parts of titanate coupling agent to 20-40 parts of 40-60% ethanol aqueous solution, stirring at a temperature of 40-60°C for 4-7h, centrifuging, washing, adding to N,N-dimethylformamide, adding 1-2 parts of succinic anhydride, stirring at 40-50°C for 1-2h, adding 1-3 parts of graphene oxide, stirring for 2-10h, centrifuging, washing, and vacuum drying to obtain activated titanium dioxide; S3, 5-10 parts of silicone resin, 5-10 parts of methyltriethoxysilane, 5-10 parts of 3-aminopropyltriethoxysilane, and activated titanium dioxide are distilled under reduced pressure for 1-2 hours, added to preform A, stirred for 1-2 hours, and distilled under reduced pressure for 1-2 hours to obtain preform B; S4. Add 1-3 parts of ultrafine bismuth oxide, 1-3 parts of surfactant, 1-3 parts of cobalt cyclohexaneate, 1-3 parts of melamine pyrophosphate, 10-15 parts of propylene glycol, and 1-3 parts of perlite to prefabricated material B, stir evenly, and wet-mill.
2. The method for preparing the environmentally friendly radiation-proof coating for construction according to claim 1, characterized in that: In S1, the vegetable oil is linseed oil or castor oil.
3. The method for preparing the environmentally friendly radiation-proof coating for construction according to claim 1, characterized in that: In S1, the particle size of barium sulfate powder is 0.1-0.2 μm.
4. The method for preparing the environmentally friendly radiation-proof coating for construction according to claim 1, characterized in that: In S2, the particle size of the nanocarbon sphere template is 100-200nm.
5. The method for preparing the environmentally friendly radiation-proof coating for construction according to claim 1, characterized in that: In S2, the titanate coupling agent is dioctyl pyrophosphoryl titanate.
6. The method for preparing the environmentally friendly radiation-proof coating for construction according to claim 1, characterized in that: In S2, the graphene oxide particle size is 10-20 μm.
7. The method for preparing the environmentally friendly radiation-proof coating for construction according to claim 1, characterized in that: In S3, the silicone resin is an environmentally friendly phenyl silicone resin.
8. The method for preparing the environmentally friendly radiation-proof coating for construction according to claim 1, characterized in that: In S4, the particle size of ultrafine bismuth oxide is 0.1-0.2 μm.
9. The method for preparing the environmentally friendly radiation-proof coating for construction according to claim 1, characterized in that: In S4, the surfactant is fatty acyl diethanolamine.
10. An environmentally friendly radiation-proof coating for construction, characterized in that: The environmentally friendly radiation-proof coating for buildings is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Vegetable oil acid modified epoxy acrylate light-cured resin and preparation method thereof
CN111777742A
Preparation method of environment-friendly low-odor water-based acrylic acid modified epoxy resin anticorrosive paint
CN118956220A
Titanium-dioxide-based double-layer hollow material, preparation method thereof, and application thereof in photocatalytic treatment of hydrogen sulfide
US20180179079A1